2020
DOI: 10.1063/1.5144288
|View full text |Cite
|
Sign up to set email alerts
|

Variational and diffusion quantum Monte Carlo calculations with the CASINO code

Abstract: We present an overview of the variational and diffusion quantum Monte Carlo methods as implemented in the CASINO program. We particularly focus on developments made in the last decade, describing state-of-the-art quantum Monte Carlo algorithms and software and discussing their strengths and their weaknesses. We review a range of recent applications of CASINO.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 123 publications
(92 citation statements)
references
References 240 publications
(369 reference statements)
2
90
0
Order By: Relevance
“…We describe the trial wave functions and the form of the single-particle orbitals used to calculate the ground-state energy of the EEBW system. We have used the casino [60] code to perform VMC calculations.…”
Section: Methodsmentioning
confidence: 99%
“…We describe the trial wave functions and the form of the single-particle orbitals used to calculate the ground-state energy of the EEBW system. We have used the casino [60] code to perform VMC calculations.…”
Section: Methodsmentioning
confidence: 99%
“…In non-covalent interactions, the challenge for FN-DMC is to provide precise and accurate evaluations of the interaction energy E int , despite E int being a tiny fraction of the total energy, e.g., it is circa 1/10 4 of the total energy in the C 60 @ [6]CPPA complex. Precision is achieved by exploiting the almost perfect scaling of DMC on modern supercomputer facilities [42][43][44] and thanks to recent algorithmic improvements which reduced the time-step bias and made DMC up to 100 times more efficient 40 . The FN-DMC setup here employed has been used and validated against experiments and CCSD(T) a number of times, for instance in refs.…”
mentioning
confidence: 99%
“…Speeding up QMC simulations has been an important focus in computational chemistry. Various software packages have been developed to this end [26,35,43]. For instance, Kim et al [26] demonstrated how DMC algorithms can be efficiently implemented on high-performance computer clusters.…”
Section: Introductionmentioning
confidence: 99%